Inherited peripheral neuropathies: Mutational analysis of cytoplasmic dyneindynactin genes and the identification of a novelautosomal recessive gene / Tey Shelisa - Tey, Shelisa (2017)
Inherited peripheral neuropathies (IPNs) are a clinically and genetically heterogeneous group of disorders affecting the peripheral nervous system. IPNs can be classified into three main groups - Hereditary Motor Neuropathies (HMN), Hereditary Sensory Neuropathies (HSN) and Hereditary Motor and Sensory Neuropathies (HMSN) which is also known as Charcot-Marie-Tooth disease (CMT), depending on the type of nerves affected. Over 80 causal genes have been reported for IPNs, yet there are many cases that remain genetically unsolved. The main objective of this study was to identify new genes associated with IPNs. A candidate gene approach was taken to screen eighteen genes within the cytoplasmic dynein-dynactin complex in 136 genetically undetermined IPN patients, whereby ten genes encoding the cytoplasmic dynein complex (DYNC1H1, DYNC1I1, DYNC1I2, DYNC1LI1, DYNC1LI2, DYNLL1, DYNLL2, DYNLT1, DYNLT3, DYNLRB1); and eight genes encoding the dynactin complex (DCTN1, DCTN2, DCTN3, DCTN4, DCTN5, DCTN6, ACTR1A, ACTR1B) were screened. In total, 25 variants were identified; however segregation analysis excluded them from being the likely cause of the disease in the respective families. In the second part of this PhD study, a consanguineous family with CMT, named CMT861, was investigated further to identify the causal gene. A combination of linkage analysis, homozygosity mapping and whole exome sequencing provided strong genetic evidence towards one candidate variant (c.A118C; p.T40P) located in AHNAK2. Gene expression analysis of AHNAK2 in cultured fibroblasts from the affected brothers showed a significant decrease at the mRNA and protein levels. Spatiotemporal expression analysis of Ahnak2 in mouse neuronal and muscle tissues suggested that this gene is a good candidate for the CMT phenotype in the family as it is expressed in the tissues that are affected in peripheral neuropathy. AHNAK2 is known to form heterodimers with iv PRX, in which PRX is a reported autosomal recessive CMT gene. PRX encodes for a protein called periaxin, which is required for myelin maintenance. We therefore hypothesise that mutations in AHNAK2 may disrupt the AHNAK2-PRX pathway and affect nerve myelination which is the most commonly affected pathway in IPN. In conclusion, although no pathogenic mutation was identified in the cytoplasmic dynein-dynactin genes, variants identified in this study could be useful as reference for other research groups in evaluating the pathogenicity of variants identified in their cohorts. Furthermore, we report the identification of AHNAK2 as a novel candidate gene for autosomal recessive CMT.